Estimating body related soft biometric traits in video frames - Arigbabu, Olasimbo Ayodeji; Syed Ahmad Abdul Rahman, Sharifah Mumtazah; Wan Adnan, Wan Azizun; Yussof, Salman; Iranmanesh, Vahab; Malallah, Fahad Layth (Hindawi Publishing Corporation, 2014)
Soft biometrics can be used as a prescreening filter, either by using single trait or by combining several traits to aid the performance of recognition systems in an unobtrusive way. In many practical visual surveillance scenarios, facial information becomes difficult to be effectively constructed due to several varying challenges. However, from distance the visual appearance of an object can be efficiently inferred, thereby providing the possibility of estimating body related information. This paper presents an approach for estimating body related soft biometrics; specifically we propose a new approach based on body measurement and artificial neural network for predicting body weight of subjects and incorporate the existing technique on single view metrology for height estimation in videos with low frame rate. Our evaluation on 1120 frame sets of 80 subjects from a newly compiled dataset shows that the mentioned soft biometric information of human subjects can be adequately predicted from set of frames.